Economic Dynamics And CO2 Emissions In Indonesia: An Analysis Of The Environmental Kuznets Curve - Dennis Aprilianti; Wiwin Priana Primadhana; Wirya Wardaya (International Journal of Economics, Business and Innovation Research, 2024)
Environmental problems are becoming more complex and profound because there is an increase in industrial and human impacts on the environment. There needs to be an effort to achieve the goal of increasing economic efficiency in several economic sectors contained in the sustainable development strategy. The purpose of this study is to analyze the kuznets hypothesis, analyze the influence of economic growth, population, foreign investment, and energy consumption on carbon dioxide emissions. This research was conducted in Indonesia. The data used is in a span of 33 years, namely from 1990 to 2022. The method used is to estimate the Environmental Kuznets Curve (EKC) hypothesis and use the Error Correction Model (ECM) analysis approach. The result of this study is that the environmental Kuznets curve hypothesis in Indonesia is proven to be relevant in the long term. The economic growth variable has a positive and significant relationship in the long term and not significant in the short term to carbon dioxide emissions. The population variable has a negative and significant relationship in the long term and not significant in the short term to carbon dioxide emissions. The long-term and short-term foreign direct investment variables have a positive and insignificant relationship with Emini carbon dioxide. Long-term and short-term energy consumption variables have a positive and significant relationship with carbon dioxide emissions.